Screening castor (Ricinus communis) genotypes for salinity tolerance in terms of germination, growth and plant ion composition - RAGHAVAIAH, CV; LAVANYA, C; KUMARAN, SHAKTI; JEEVANROYAL, TJ (The Indian Journal of Agricultural Sciences, 2011)
Pot culture experiments were conducted during 2001-02 and 2002-03 at the Directorate of Oilseeds Research, Hyderabad to evaluate 20 genotypes of castor ('DCS 89', '481', 'DCH 177', 'VP 1', 'GC-2', 'LRES 17', 'DCS9', 'DCS86', 'GCH 5' 'DeS 33', 'TMV 5', 'TMV 6', 'DCH 149', 'DPC9', ~DCH 151" 'GCH4', 'DCS5', 'Aruna', 'DCH32'and 'Kranti') under 4 levels of salinity ( ECe